Towards a~guide for developers and novice researchers on human-centered design of the take-over request—Combining user experience and human factors - Alisa Lindner; Tanja Stoll (Zeitschrift für Arbeitswissenschaft, 2022)
With major developments in road traffic, especially automated and connected driving, new challenges in designing human-vehicle interaction arise. Human Factors is a~field of research that analyzes the interaction between humans and systems to reduce error and increase productivity, safety and comfort. Related to that, User Experience (UX) Design is based on the human-centered design process and the principle of considering human needs throughout the development cycle. We highlight similarities and differences and discuss how the combination of these two disciplines can help developers facing one of the urgent challenges in automated driving: the design of take-over scenarios from automated to manual driving. To address this question, we present an exemplary process flow that combines elements of Human Factors and UX Design in order to develop safe and pleasant to use solutions. In this context, relevant theoretical models and practical methods are discussed. Practical Relevance : This paper aims to guide an interdisciplinary development team through the design of the take-over scenario using the human-centered design process (ISO 2019): Phase~(0) problem statement; (1~&~2) understand the context of use and identify user requirements; (3)~formulate meaningful How-might-we questions and generate ideas; and (4)~collect user feedback to evaluate the designed solution. This article provides starting points for both researchers in academia as well as developers in the industry and contributes to the lively discourse about the self-image of human-centered design and corresponding disciplines.
Keywords: 650; User experience; Human-machine interaction; Challenges of automated driving; Take-over; Human-centered design; Human factors